2021
DOI: 10.1002/jemt.23985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanical and optical properties of a newly marketed universal composite resin with contemporary universal composite resins: An in vitro study

Abstract: The purpose of this study was to evaluate the surface roughness, microhardness, color change, and translucency of a newly marketed universal nanohybrid composite resin (CR) (G-aenial A'CHORD) comparing with four contemporary universal CRs including two nanofilled (Filtek and Estelite Asteria) and two nanohybrid CRs (Charisma Dimond and Neo Spectra ST HV in vitro). Sixty-five specimens (8.0 mm  2.0 mm) were fabricated (n = 13, per group). After finishing and polishing, specimens were subjected to surface rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…The results described in the current study concur with those obtained by Gurgan et al [ 27 ] for the color stability of Filtek Universal and G-ænial A´chord. Those authors also found that G-ænial A´chord presented excellent optical properties, which are features supported by the improved polishing properties of these nano-hybrid composite resins [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results described in the current study concur with those obtained by Gurgan et al [ 27 ] for the color stability of Filtek Universal and G-ænial A´chord. Those authors also found that G-ænial A´chord presented excellent optical properties, which are features supported by the improved polishing properties of these nano-hybrid composite resins [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it has a low viscosity, which makes it easy to model. It can be applied using the layer technique as well as a single layer [18] and has enhanced aesthetic properties for fillings in the anterior and lateral dental arch [19].…”
Section: Methodsmentioning
confidence: 99%
“…However, the improvements in esthetic materials and techniques have facilitated the road to esthetic restorations, in terms of simplifying the shade selection. 1,8 Accordingly, it is the level of optical determinants as well as the filler technology and contents that generates the esthetic qualification of the final restoration. [7][8][9][10] Proper material and shade selection, and appropriate layering protocol should be determined to obtain an optimal esthetic result.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 Accordingly, it is the level of optical determinants as well as the filler technology and contents that generates the esthetic qualification of the final restoration. [7][8][9][10] Proper material and shade selection, and appropriate layering protocol should be determined to obtain an optimal esthetic result. 1,5 Following the developments in contemporary composite kits, microfilled resins evolved into microhybrid and nanohybrid/nanofilled resins.…”
Section: Introductionmentioning
confidence: 99%